1975
DOI: 10.1001/archneur.1975.00490470079012
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Toxoplasmosis

Abstract: The neurological manifestations of six cases of acquired central nervous system toxoplasmosis are compared with the 39 well-documented cases from the literature. Half of the patients had underlying systemic diseases (18 malignant neoplasms, two renal transplants, three collagen vascular diseases) treated with intensive immunosuppressive therapy. The remainder had primary toxoplasmosis. Three major neurological patterns were seen: (1) diffuse encephalopathy with or without seizures, (2) meningoencephalitis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
2

Year Published

1977
1977
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…The microscopic lesions found were consistent to the ones reported by other authors which studied lesions in humans [7,9,11]. This study confirms the importance of T. gondii as a cause of active and severe lesion in the central nervous system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The microscopic lesions found were consistent to the ones reported by other authors which studied lesions in humans [7,9,11]. This study confirms the importance of T. gondii as a cause of active and severe lesion in the central nervous system.…”
Section: Discussionsupporting
confidence: 92%
“…Amongst the symptomatic forms, the neurological involvement is the most common, observed as encephalitis or meningoencephalitis with unspecific symptoms [3]. The beginning may be marked by cephalalgia, somnolence and behavioral changes, during from days to weeks, followed by coma, convulsions, pyramidal or cerebellar syndrome, ophthalmologic paralysis and psychic alterations [3][4][5][6][7][8]. The encephalitis usually is diffuse and focal lesions leading to localized manifestations are rarely observed [5,7].…”
mentioning
confidence: 99%
“…Diffuse toxoplasmosis with CNS involvement is a life-threatening disease which often avoids diagnosis (1, 8). In a review of 45 patients with CNS-toxoplasmosis, less than 40% were diagnosed prior to death.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 45 patients with CNS-toxoplasmosis, less than 40% were diagnosed prior to death. However, early diagnosis of the disease has been rewarded by a rapid response to treatment (8). …”
Section: Discussionmentioning
confidence: 99%
“…3,[28][29][30] Studies have shown that in recrudescent toxoplasmosis, Toxoplasma tachyzoites or antigens were associated with microglial nodules that were not found in the adjacent parenchyma. 31,32 The presence of mononuclear cells and the availability of antigens provide a favorable condition for activation of macrophages to synthesize and release enzymes.…”
Section: Discussionmentioning
confidence: 99%